GENDER WISE COMPARISON OF DISORDERED EATING ATTITUDES IN PHYSICAL EDUCATION PROFESSIONALS OF INDIA: A CROSS-SECTIONAL STUDY - Bhagi, Jupender Singh; Kaur, Kuljeet; Tyagi, Dr. Sarita (International Journal of Research -GRANTHAALAYAH, 2021)
Motivation/Background: Eating disorders (ED) are serious psychological disorders characterized by unhealthy eating habits. There are a limited number of studies on eating disorders among male and female physical education professionals like teachers, coaches, and trainers. Therefore, the objective of this study was to examine the prevalence of disordered eating attitudes (EA) among the ones that are more or less associated with fitness, training and counseling the students and public in general. Method: A survey study on 83 such professionals with at least 5 years of experience was being conducted through online questionnaire. The Eating Attitudes Test (EAT-26) was used. Results: Of the 83 participants, 20% scored ≥ 20 on the EAT-26. A significant positive correlation (p<.01) was found between age and body mass index (BMI) on EAT-26 scores. Conclusions: Awareness regarding appropriate nutrition in relation to body weight is needed among professionals themselves before they counsel others to begin with and must therefore be cautious about their own eating patterns in the first place.